2020
DOI: 10.21106/ijma.401
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Child Vaccination: A Systematic Approach to Closing the Immunization Gap

Abstract: The COVID-19 pandemic threatens to set back major successes that have been achieved in global vaccine initiatives. We conducted a rapid review and synthesis of the literature on immunization provision and Utilization since the onset of the COVID-19 pandemic. A total of 11 papers comprising peer-reviewed articles and key policies and guidelines, published between January 1 and June 15, 2020, were analyzed. Widespread disruptions of routine immunization and vaccination campaigns were reported leaving millions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…1 Specifically in the case of childhood immunizations, campaigns were interrupted and concerns about bringing children to health facilities have contributed to reducing coverage. 2, 3 Yet, a modeling exercise for Sub-Saharan Africa suggested that child deaths due to vaccine-preventable diseases would far exceed the number of childhood deaths due to COVID-19 illness acquired during visits to health facilities in order to receive vaccines. 4…”
Section: Introductionmentioning
confidence: 99%
“…1 Specifically in the case of childhood immunizations, campaigns were interrupted and concerns about bringing children to health facilities have contributed to reducing coverage. 2, 3 Yet, a modeling exercise for Sub-Saharan Africa suggested that child deaths due to vaccine-preventable diseases would far exceed the number of childhood deaths due to COVID-19 illness acquired during visits to health facilities in order to receive vaccines. 4…”
Section: Introductionmentioning
confidence: 99%
“…25 The mitigation measures adopted to control the COVID-19 pandemic threaten to undo the progress achieved in the control of vaccine-preventable diseases in low-and middle-income countries and high-income countries. 26 From the major reasons for vaccination failure among partially vaccinated children; there are religious and cultural barriers that account 6(9.7%) of all reasons. This might be due to missed understanding or miss interpretation of religious and cultural concepts or views of child vaccination.…”
mentioning
confidence: 99%
“… [31] , [32] As this study has shown, countries also need to now consider how to address missed vaccination due to COVID-19, and guidance is available. [14] , [33] Foresight and a comprehensive plan for rapidly closing this immunization gaps is crucial, [12] , [34] including immediate planning for detecting individuals who have missed vaccination, instituting large-scale catch-up programs and campaigns, and bridging any delivery gaps. [12] , [35] , [36] Using shorter time periods to monitor vaccination uptake during the pandemic is advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…[12] This deferral has affected an estimated 80 million children under age one. [13] Substantial missed or delayed routine vaccinations can trigger secondary outbreaks of vaccine-preventable diseases and associated mortality, [2] , [3] , [14] , [15] similar to the Ebola outbreak in west Africa where reallocation of health resources decreased vaccination coverage and resulted in disease outbreaks. [16] …”
Section: Introductionmentioning
confidence: 99%